DEVELOPMENT OF THE MUNICIPAL BOND MARKET IN POLAND AFTER 1989 - Galiński, Paweł (Ekonomika, 2013)
Abstract. The purpose of the paper is to present the development of the municipal bond market in Poland between 1989 and 2012, a characteristic of municipal bonds and their types, issued in this period. The empirical research conducted by the author provides some main financial indicators that determine the development of this market and its role for local governments in Poland. Moreover, there are analysed the types of investors on this market, organizers of the placements or the meaning of this market against the background of the municipal bond markets in the European Union (EU) countries. The study is mainly based on the miscellaneous reports and statistics of the National Bank of Poland, Ministry of Finance, Central Statistical Office of Poland, Warsaw Stock Exchange or rating agency Fitch Polska. An important source of information was also the research conducted by the author, which concerned the perspective of servicing the local governments by commercial banks and the associated risk. As a consequence, the author indicates that the value of municipal bonds issued in Poland is still relatively low in comparison with its gross domestic product and the leading EU countries. Therefore, there are possibilities of the further growth of this market in Poland. First and foremost, municipal bonds are positively perceived as an investment instrument by the investors, i.e. mainly commercial banks. Besides, these securities have a small share in the investment portfolio of pension funds and investment funds. However, one of the main obstacles of the further development of the municipal bond market in Poland is its relatively low liquidity.Key words: municipal bond market, municipal bonds, local governments